Glandular cell abnormalities in cervical cytology: What has changed in this decade and what has not?. (September 2019) - Kumar, Neeta; Gupta, Ruchika; Gupta, Sanjay
Abstract: The relative as well as absolute increase in cervical adenocarcinomas has brought the glandular lesions of cervix into attention of the cytologists and molecular biologists alike. Though the cytologic criteria for diagnosis of these lesions have been refined to a great extent through the evolution of the Bethesda System for reporting cervical smears, still some challenges exist regarding an accurate recognition of glandular cell changes in cervical smears and molecular tests to aid their detection. The present review is a narrative compilation of the current status of identification of cervical glandular abnormalities in the smear, the changing scenario of their histologic outcomes, newer entities within the category of glandular lesions and molecular cytology as relevant to this topic. The script also briefly explores the role of HPV DNA testing, the outcomes of HPV-positive and negative glandular abnormalities and the potential status of glandular lesions in the wake of implementation of HPV vaccination. Though this review is not an exhaustive one, it aims to put the issues pertaining to cervical glandular abnormalities into perspective and to explore the future research directions.